Δβ-Thalassaemia in two Turkish families. Issue 4 (December 1974) - Aksoy, Muzaffer; Erdem, SŃakir; Dinçol, Günçaǧ
Abstract : Two Turkish families with δβ-thalassaemia are presented. Two sibs belonging to one of these families were doubly heterozygous for both δβ-thalassaemia and β-thalassaemia. The levels of fetal haemoglobin in these two sibs were quite different, namely 49·5 and 75·6%, respectively. The problem of δβ-thalassaemia in Turkey is discussed.